Improving real-time multimedia scheduling in practical mobile cellular channels - Mohd. Ramli, Huda Adibah; Mohd. Isa, Farah Nadia (UTP Press, 2016)
The demand for real-time multimedia applications has been exponentially increased these days. Long Term Evolution-Advanced (LTE-A) is one of the mobile cellular technologies envisaged to provide good real-time multimedia experiences. However, real-time multimedia scheduling over the downlink LTE-A is a subject to various impairments. This paper adapts the well-known single-carrier Maximum-Largest Delay First (M-LWDF) algorithm into practical multi-carrier downlink LTE-A so as to minimize the detrimental effects of mobile cellular channel impairments on the real-time multimedia experiences. Simulation results demonstrated the efficacy of the adapted M-LWDF algorithm where it provides good experiences for more users and is more robust in case of outdated channel quality information report